Transcutaneous bilirubin-based screening reduces the need for blood exchange transfusion in Myanmar newborns: A single-center, retrospective study - Suzuki, Hiromi; Yasuda, Saneyuki; Htun, Yinmon; Aye, Nant San San; Oo, Hnin; Oo, Thet Paing; Htut, Zaw Lin; Koyano, Kosuke; Nakamura, Shinji; Kusaka, Takashi (Frontiers in Pediatrics, 2022)
Background: Neonatal hyperbilirubinemia is a significant health problem in Myanmar. We introduced transcutaneous bilirubin (TcB) measurements in 2017 and developed an hour-specific TcB nomogram for early detection and treatment of hyperbilirubinemia in Myanmar neonates. This study aimed to evaluate whether our screening method for hyperbilirubinemia decreased the requirement of blood exchange therapy (ET). Methods: This retrospective cohort study was conducted at the Central Women’s Hospital, Yangon. Two groups were included as follows: group 1 (control group; comprising infants born in 2016 and screened on the basis of Kramer’s rule), and group 2 (intervention group; comprising infants born in 2019 and screened by TcB measurement using a nomogram). The number of ETs was analyzed based on causes of hyperbilirubinemia and number of days after birth. Results: Groups 1 and 2 comprised 12,968 and 10,090 infants, respectively. Forty-six and two infants in Groups 1 and 2, respectively, required an ET. The odds ratio for ET was 18.0 (Group 1 to Group 2; 95% confidence interval [CI]: 4.8–67.1; p = 0.000). An analysis of 46 ET cases in Group 1 revealed G6PD deficiency as the major cause of neonatal hyperbilirubinemia in 37 cases (80.4%). In Group 2, no ET case had G6PD deficiency. Conclusions: The management of hyperbilirubinemia using our screening method (TcB Nomogram) can effectively reduce the need for ET in neonates in Myanmar.